Being Faithful, Condom Use, No Drug Use and Circumcision Behavior in Men Sex with Men Group - Fatiah, Mona Safitri (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Men Sex Men (MSM) adolescents and young adults living with Sexually Transmitted Infections (STIs) in Indonesia is about 19.3%; the transmission occurs if they do not apply the behavior of be faithful, Condom use, no Drug use and circumcision. The purpose of study is to see the effect of BCD and circumcision behavior on the incidence of STI in young MSM in Indonesia.Method: Integrated Biological Behavior Survey (IBBS) data was the main data source used in this study, with the research design applied was a cross-sectional study. The study population was MSM spread across 24 provinces in Indonesia totaling 6,000 people and the sample used was MSM aged between 15-25 years around 2,200 people, sample selection using Respondent Driven Sampling (RDS) technique, where data testing used logistic regression test risk factor model using STATA 16 data processing software.Result: MSM suffering from STI had one of the STI symptoms (76.9%). Results: partner fidelity (AOR: 0.44; 95% CI: 0.08-2.64), condom use (AOR: 0.47; 95% CI: 0.16-0.78), needle and syringe drug use (AOR: 0.49; 95% CI: 0.28-0.71) and circumcision behavior (AOR: 1.22; 95% CI: 0.98-1.45) appeared to be associated with STI incidence in Indonesia after controlling for the variables of frequency of anal sex, frequency of HIV testing and STI testing behavior. Conclusions: BCD and circumcision behavior is one of the easy-to-implement alternatives to prevent STI transmission among young MSM.